2017
DOI: 10.18632/oncotarget.19184
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node ratio, but not the total number of examined lymph nodes or lymph node metastasis, is a predictor of overall survival for pancreatic neuroendocrine neoplasms after surgical resection

Abstract: AimTo evaluate the prognostic significance of lymph node metastasis, extent of examined lymph nodes (ELNs) and lymph node ratio (LNR) for resected pancreatic neuroendocrine neoplasms (pNENs).Materials and MethodsSurgically resected pNENs were assimilated from the Surveillance, Epidemiology, and End Results database. Kaplan-Meier and Cox proportional hazard models were used to examine the prognostic effect of clinicopathological characteristics on overall survival; Harrell’s concordance index was performed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…Except the TNM staging system, there are a plethora of other indicators for the prognosis of pNET patients. Through our analysis, the grade, surgery, age and sex were independent predictors for OS, consistent to the previous reports 27 , 32 . Grade reflected tumor biological behavior and was closely connected to its prognosis 33 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Except the TNM staging system, there are a plethora of other indicators for the prognosis of pNET patients. Through our analysis, the grade, surgery, age and sex were independent predictors for OS, consistent to the previous reports 27 , 32 . Grade reflected tumor biological behavior and was closely connected to its prognosis 33 .…”
Section: Discussionsupporting
confidence: 91%
“…Controversy still remains on whether the patients' survival is related to lymph node metastasis 24 - 27 . Although Krampit et al 25 had considered the links between the number of lymph nodes and survival, he just applied two lymph nodes as the cut-off value, which was limited and blurry.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the multivariate analysis demonstrated that LN metastases were not an independent prognostic factor for patients (Table ). A similar result was also found in Peng's study, and they demonstrated that an LN‐positive ratio greater than 0.4 was an independent risk factor for pancreatic NENs . Therefore, the LN‐positive ratio may be a strong predictive factor for identifying high‐risk patients.…”
Section: Discussionsupporting
confidence: 83%
“…However, the minimum number of TLN examined in PD is controversial. The AJCC staging system recommends at least 12 harvested nodes for accurate staging because insufficient LNs may lead to under-stage the N category in many kinds of tumors, such as gastric carcinoma or pancreatic carcinoma 1 , 17 - 20 . In some studies, the overall number of TLN was relatively small when PD was performed 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%